2005
DOI: 10.1097/00001756-200504040-00002
|View full text |Cite
|
Sign up to set email alerts
|

A neuronal cell line that does not express either prion or doppel proteins

Abstract: Prions have been extensively studied since they represent a new class of infectious agents, the pathogenic prion protein (PrPSc). However, a central question on the physiological function of the normal prion protein (PrPC) remains unresolved. A cell model which was previously established from Rikn mice (PrP-/-) remains problematic because of its ectopic expression of the doppel (Dpl) which may have a neurotoxic effect. Here we established neuronal cell lines from Zürich I (PrP-/-) which do not express Dpl prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…(Steele et al, 2006). Surprisingly, previous in vitro studies showed that PrP c -deficient neural cell lines derived from embryonic hippocampus display higher proliferative rates than WT cells in culture (Kim et al, 2005). As indicated above, recent results from our group demonstrate PrP c expression in remnant oligodendrocyte progenitor cells located in the adult neural parenchyma that normally proliferate (Fontana et al, unpublished data).…”
Section: However Contradictory Results Using Other Neoplastic and VImentioning
confidence: 75%
See 1 more Smart Citation
“…(Steele et al, 2006). Surprisingly, previous in vitro studies showed that PrP c -deficient neural cell lines derived from embryonic hippocampus display higher proliferative rates than WT cells in culture (Kim et al, 2005). As indicated above, recent results from our group demonstrate PrP c expression in remnant oligodendrocyte progenitor cells located in the adult neural parenchyma that normally proliferate (Fontana et al, unpublished data).…”
Section: However Contradictory Results Using Other Neoplastic and VImentioning
confidence: 75%
“…In consequence, the generation of neuronal lines has supposed new models for the in vitro study of the PrP c -PrP sc interaction. For example, a neural line derived from Zürich I mice which do not express Dpl have shown neuronal features (Kim et al, 2005). Thus, it would be feasible to induce differential levels of PrP c expression or to alter other important factors (like PrP c cytoplasm/membrane localization, trafficking or glycosilation) in order to study how PrP sc invasion/toxicity is modulated.…”
Section: Prp C Expression and Prion Pathologymentioning
confidence: 99%
“…38,39 To investigate further a mechanism for the protective role of PrP C in oxidative stress, we examined the alteration and differentiation of autophagy under H 2 O 2 -induced oxidative stress in hippocampal neuronal cell lines expressing PrP C (Prnp +/+ ) and a control vector (Prnp 0/0 ). 36,40 In addition, we explored whether the inhibition or induction of autophagy could promote cell survival or cell death. In these experiments, we show that the expression of the autophagy marker LC3B-II was more increased in (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Zpl 2-1-PrP cells were found more sensitive when assayed for cell viability (alamarBlue) and less sensitive when assayed by dye-exclusion (propidium-iodide) than ZW 13-2 cells ( Figure 19C Figure 18 and 19 are varied among the four metals, which in turn suggest no identical mechanism of actions nor common way of interference for PrP. These results also show that the methods used might be influential, and these might contribute to the differences seen in respect to the role of PrP in transition metal toxicities of F14, CF10, A74 and Zpl cells (Choi et al, 2007;Haigh and Brown, 2006;Kim et al, 2005;Rachidi et al, 2003b).…”
Section: Discussionmentioning
confidence: 94%
“…The prion protein's role in a particular cellular process, including those that are concerned with metal-PrP interrelations in ex-vivo and in-vivo systems are generally studied by either genetically ablating (Büeler et al, 1992;Haigh and Brown, 2006;Kim et al, 2005;Kuwahara et al, 1999;Rossi et al, 2001;Sakaguchi et al, 1996) or siRNA silencing (Loubet et al, 2012) while working on HeLa cells (Molnár et al, 2013)., and have used here similarly. The bright red immunofluorescence-staining pattern in the ZW 13-2 cells revealed that the prion protein was distributed on the surface of the cells, whereas no immunoreactivity was detected in the Zpl 2-1 cells.…”
Section: Resultsmentioning
confidence: 99%